Akhmad Tashkuprizada’s Approach to the Issues of Islamic Law - Ergashev Urolbek Berkinovich (Pubmedia Social Sciences and Humanities, 2026)
This article is devoted to the analysis of the work “Risala fi az-zebbi an-harimi ash-shari’at” (On the Protection of Sharia Laws) written by Akhmad Tashkuprizada in order to explain the controversial Sharia issues he encountered during his time as a judge. This work is considered an important work that deserves attention from the point of view of the legal thought of the Ottoman Empire. In this work, Akhmad Tashkuprizada provides important information about anger, justice, courage and the limits of the judgeship, the functioning of the judicial system of the Ottoman Empire, the social responsibility and moral qualities of judges.